Pola Kristalisasi Garam Dalam Kondisi Lingkungan Ekstrem - Azizah, Ainiyatul; Angelina, Nania Nova (Journal of Science and Technology: Alpha, 2025)
Salt crystallization is a fundamental process that is greatly influenced by environmental conditions, including temperature, humidity, pressure, and atmospheric composition. This study aims to analyze salt crystallization patterns occurring under extreme environmental conditions, such as high temperatures, very low humidity, as well as hypersaline and low-temperature environments. The methods used include laboratory experiments with simulated extreme environments using a climate control chamber and microscopic analysis of the shape and structure of the resulting salt crystals. The research findings show that extreme environmental conditions significantly affect the morphology and growth rate of salt crystals. Under high temperatures and low humidity, crystals tend to form complex dendritic structures with higher growth rates. Conversely, at low temperatures and high pressure, crystals tend to form cubic shapes with denser structures and slower growth. Hypersaline environments exhibit unique crystallization patterns, including the formation of irregularly shaped crystals and non-homogeneous surface patterns. These findings are important for further understanding of natural geochemical processes in extreme environments such as salt deserts, hypersaline lakes, or extraterrestrial planets like Mars. In addition, the results can be applied to desalination technology and more efficient industrial salt production.